O ambiente interno ideal para o desenvolvimento de equipes: um estudo sob os olhares de profissionais coaches - GONÇALVES JUNIOR, Antônio Otávio Alves (2015)
This work aims to verify if the organizational environment actually perceived by coaches leaders in fact can contribute to the growth of the company. One of the existing job opportunities in the traditional coaching guidelines is in the direction of the organization's efforts to manage, train and align the interests of its employees to the corporate's strategic objectives. In a scenario like this the techniques applied by a coach leader can be very useful provided the organizational setting print a culture and climate favorable to the rules and practice philosophies. To achieve the specific goal for this thesis a literature survey was conducted to understand the extent and limits of coaching techniques and lift which variables can influence the proposed use of the method. Once fulfilled this step was necessary to conduct a descriptive study of qualitative character in an attempt to capture the impression of coaches leaders about what they are experienced in the business market in Salvador. The script includes built research questions about the culture, environment, climate and allows the researcher to outline a scenario that possibly is ideal for the coaching techniques can bring significant results to companies in a broad sense.